The granitic rocks and associated auriferous mineralization, in the Eastern Cordillera of North Peru, 6º 30’– 7º 30’ - Sánchez Fernández, Agapito Wilfredo (2006)
In the northern part of Peru, between Marañon river and the Eastern Cordillera is located the Gollón – Callangate Batholith shaped by discontinuous plutonic bodies along 100 kilometers, from Santo Tomas to Bambamarca. Its host are metamorphic rocks of the Marañon Complex and sedimentary rocks of Lower Paleozoic age. The batholith has as components mainly medium grain sized granodiorites to tonalites (Gollón, Balsas, Lavador and Los Alisos units) monzogranites (Abra Chanchillo, Yalen, Enaben, Callangate units) and syenogranites (Chacanto unit). Their textures and structures are primary, isotropic. The most common minerals are: plagioclase, K felspar, quartz, biotite, hornblende, and apatite, zircon, magnetite as accessories. In the units Gollón, Lavador, schists of Marañon Complex and slaty pelites (Contaya Formation) are found seams of quartz with Au contents. Quartz veins with Au contents are more frequent in granitic rocks, in general follow a NW - SE trend with inclinations of 30º to 75º towards the NE and thickness between 0,2 to 1,2 meters. The veins in the metamorphic complex are irregular, agree with schistosity N 40º - 50º W, inclined to NE (El Reo and Horabuena. Au quartz veins have three stages of formation, initial stage with milky quartz, rutile, stage I gray quartz with sulphides (pyrite,sphalerite, calcopyrite, muscovite in alterations), then in stage II solutions precipitate gray quartz, galena, sulfosales, electrum, native gold and silver. Later supergene alteration give as a result formation of covelite, hematite-limonite, manganese hydroxides, carbonates. Major elements expressed as AFM diagram, and SiO2 plotted against K2O + Na2O y K2O indicate that granitic rocks from the Gollón – Callangate Batholith are calc alkaline, subalkaline and mainly have high K content. Meanwhile trace elements in an spider diagram generates a graphic interpreted as typical of subduction environment. Plutonic rocks of the Gollón Callangate Batholith according fields relationships are Lower Missisipian - Lower Pensilvanian, Some radiometric published data (Sánchez A., 1995) have given ages of 346 - 329 million years for the Balsas and Callangate Units. Gold mineralization should have been emplaced during early Pensilvanian, after a correlation with Pataz area. Major potential structures related to gold content are those located in tonalites –granodiorites of medium grain, following regional structure. Likewise those veins in greenschists associated with mafic dikes.